Thermodynamics and Chemistry - DeVoe, Howard (Open textbook library., 2020)
Thermodynamics and Chemistry is designed primarily as a textbook for a one-semester course in classical chemical thermodynamics at the graduate or undergraduate level. It can also serve as a supplementary text and thermodynamics reference source.